Thinking and Working Politically: What does it mean, Why is it important and How do you do it? - and Leftwich, Adrian (DLP, 2011)
This paper suggests that working politically in a developmental context means directing attention and support to the agents of reform and development (leaders and organisations). This allows investment in the local processes that will resolve problems – such as problems of collective action – through the work of alliances and coalitions. Hence, it will drive the formation and consolidation of the locally appropriate, feasible and legitimate institutions that are most likely to advance development outcomes. The Developmental Leadership Program defines politics as the pervasive, unavoidable and necessary activities of conflict, negotiation and compromise involved in group decision-making about how resources are to be used, produced and distributed. Thinking politically means understanding that both political and technical dimensions are central to developmental outcomes. It also means: Understanding that ‘agency’ matters. That is, that people have the potential to change things, but always withhin the context of given institutional arrangements, which contain both constraints and opportunities. Leaders, organisations and followers think, strategise and attempt to resolve problems in different ways in the same contexts. Understanding leadership as a political process that mobilises people and resources in support of a goal: leaders seldom work on their own. Realising that overcoming collective action problems is a major challenge of development. Collective action problems occur when people with diverse (often competing) interests struggle to agree on an organisational arrangement from which they would all benefit. Understanding that coalitions (formal or informal) are a crucial political mechanism for the resolution of collective action problems. Paying attention to the detailed inner politics of regimes, sectors or issues (‘micro-politics’). This includes understanding who the players are, where they come from, their organisational affiliations, ideologies and interests and the political dynamics involved. (Many political analysis tools are inadequate for this level of detail.) Recognising that processes are as important as projects in development, and vary from context to context. Working politically in development means supporting, brokering, facilitating and aiding the emergence and practices of (public or private) developmental or reform leaderships, organisations, networks and coalitions at any level, and across all sectors. It means helping them to respond to, and work with, initiatives and requests from local individuals and groups. Working politically can also involve: Investing in the effectiveness of developmental coalitions by enhancing the political capacity of organisations in negotiation, advocacy, communication and the generation of constructive policy options. Rethinking higher educational support programmes so that they supplement a skills focus with strategies that help to build networks, and encourage the understanding of collective action problems and of the importance of providing public goods. Acquiring a deep and detailed knowledge of, and long-term exposure to, the country or issue concerned. Respectful and sensitive understanding of local political dynamics and cultural norms. Employing more social scientists and a well-trained, politically savvy workforce, both local and international, with the capacity to ‘read’ the politics. In particular, coalitions can help drive the endogenous politics of developmental reforms by: 1) achieving a specific policy goal; 2) opening up debate on a previously taboo issue; 3) deepening and strengthening the coalition’s internal organisation and relationships for future purposes; and 4) increasing the capacity of constituent organisations. It is also important to understand that: Developmental leaderships and coalitions often emerge in response to a critical juncture – a threat, challenge or danger – or a new opportunity. What matters is whether leaders have the knowledge, education, vision, prior experience and networks to seize such opportunities. The character and conditionality of funding by donors or supporters can make or break a coalition. Are tight conditions applied? Are funding arrangements transparent?